Non-pharmacological interventions for schizophrenia-analysis of treatment guidelines and implementation in 12 Southeast European countries - Stevović Injac, Lidija; Repišti, Selman; Radojičić, Tamara; Sartorius, Norman; Tomori, Sonila; Kulenović Džubur, Alma; Popova, Ana; Kuzman Rojnić, Martina; Vlachos, Ilias I; Statovci, Shukrije; Bandati, Alexei; Novotni, A; et al. (Springer Science and Business Media LLC, 2022)
This study aimed to analyze treatment guidelines of 12 SEE countries to identify non-pharmacological interventions recommended for schizophrenia, explore the evidence base supporting recommendations, and assess the implementation of recommended interventions. Desk and content analysis were employed to analyze the guidelines. Experts were surveyed across the 12 countries to assess availability of non-pharmacological treatments in leading mental health institutions, staff training, and inclusion in the official service price list. Most SEE countries have published treatment guidelines for schizophrenia focused on pharmacotherapy. Nine countries-Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Moldova, Montenegro, North Macedonia, and Serbia-included non-pharmacological interventions. The remaining three countries-Kosovo (UN Resolution), Romania, and Slovenia-have not published such treatment guidelines, however they are on offer in leading institutions. The median number of recommended interventions was seven (range 5-11). Family therapy and psychoeducation were recommended in most treatment guidelines. The majority of recommended interventions have a negative or mixed randomized controlled trial evidence base. A small proportion of leading mental health institutions includes these interventions in their official service price list. The interventions recommended in the treatment guidelines seem to be rarely implemented within mental health services in the SEE countries.